2002
DOI: 10.1097/00008571-200210000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Deposition of Alzheimer's ??-amyloid is inversely correlated with P-glycoprotein expression in the brains of elderly non-demented humans

Abstract: Deposition of the beta-amyloid peptide (Abeta) in the brain occurs during normal ageing and is substantially accelerated in patients with Alzheimer's disease. Since Abeta is continuously produced in the brain, it has been suggested that a clearance mechanism should exist to prevent its accumulation and subsequent aggregation. Until now, little attention has been paid to the possible role of P-glycoprotein (P-gp), a member of the ATP binding cassette superfamily of transporter proteins, in the pathogenesis of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
223
1
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 316 publications
(241 citation statements)
references
References 32 publications
15
223
1
2
Order By: Relevance
“…However, a comparison of cell systems and membrane assays have been recently described and as far as these studies are concerned it results that all compounds positive in the ATPase membrane assay are also potential substrates (Adachi et al, 2001;Polli et al, 2001). It has been proposed that the expression pattern of P-gp has a key role in the pathogenesis of brain diseases such as Alzheimer's disease (Vogelgesang et al, 2002), Parkinson's disease (Kortekaas et al, 2005) and brain HIV infection (Langford et al, 2004). ALS would seem to be no exception, although a more detailed analysis on the expression of P-gp and other drug efflux transporters in ALS mice and in human specimens would need to be undertaken.…”
Section: Discussionmentioning
confidence: 99%
“…However, a comparison of cell systems and membrane assays have been recently described and as far as these studies are concerned it results that all compounds positive in the ATPase membrane assay are also potential substrates (Adachi et al, 2001;Polli et al, 2001). It has been proposed that the expression pattern of P-gp has a key role in the pathogenesis of brain diseases such as Alzheimer's disease (Vogelgesang et al, 2002), Parkinson's disease (Kortekaas et al, 2005) and brain HIV infection (Langford et al, 2004). ALS would seem to be no exception, although a more detailed analysis on the expression of P-gp and other drug efflux transporters in ALS mice and in human specimens would need to be undertaken.…”
Section: Discussionmentioning
confidence: 99%
“…One example is the multidrug transporter P-glycoprotein (Pgp). Evidence supporting this role for Pgp includes: (1) observations of Pgp-dependent efflux of Ab in vitro, 59,60 (2) an inverse correlation of Ab deposition and microvascular Pgp expression in human brain tissue, 61 (3) decreased Ab efflux and enhanced Ab deposition in mice that lack Pgp, 62 (4) impaired microvascular Pgp function in a transgenic AD mouse model that is restored by pharmacologic intervention shows corresponding improvement in Ab efflux and reduced Ab deposition, 62,63 and (5) showing Pgp dysfunction in human AD using clinical PET imaging studies. 64 Because of its luminal location, 65 it has been proposed that Pgp facilitates the extrusion of Ab from the endothelial cell into the bloodstream after Ab has been internalized from brain interstitial fluid (ISF) by LRP-1.…”
Section: Defects In Blood-brain Barrier Transporters That May Contribmentioning
confidence: 99%
“…These results clearly indicate the need for further investigations about the role of ABCG2 in the pathology of AD and confirm the validity of its therapeutic targeting in the treatment of AD, 62,63,125 or its utilization as a biomarker of CAA vascular pathology in AD. 124 Furthermore, taking into consideration that ABCB1 and ABCG2 are both involved in limiting Aβ access to the brain by clearance and/or extrusion, and that in AD brains while expression of ABCB1 is down-regulated 55 increased expression of ABCG2 has been observed, 124 studies investigating both transporters' expressions simultaneously in the same affected brain region are warranted. This is important to establish increased expression of ABCG2 as a compensatory mechanism for ABCB1 down-regulation and as one way to protect the brain.…”
Section: ■ Abcg Family Abcg2 (Breast Cancer Resistance Protein Bcrp)mentioning
confidence: 99%
“…52−56 Studies have demonstrated a progressive decline in the level of ABCB1 at the BBB during normal aging, and this decline was positively correlated with accumulation of Aβ in AD. 55,57 In vitro binding studies showed that efflux of Aβ 40 and Aβ 42 are mediated by ABCB1 as a result of direct interaction between Aβ and ABCB1. 52 This observation was then followed by several in vitro and in vivo studies demonstrating the ABCB1 role in the clearance of Aβ from the abluminal to the luminal side of the membrane.…”
mentioning
confidence: 99%